Comparative Study of Lipid and Fatty Acid Profile in Liver Tissues of Male and Female Silurus triostegus During the Catching Seasons - Semra Kaçar; Mehmet Başhan (Aquatic Sciences and Engineering, 2021)
In this study, seasonal variations of total fatty acid (FA), phospholipid (PL) and triacylglycerol (TAG) compositions in liver tissues of catfish (Silurus triostegus) were investigated. Samples of S. trioste-gus were obtained from Atatürk Dam Lake, Turkey, in two month periods during one year as from May. The major components were palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1n-9), palmi-toleicacid(16:1n-7),docosahexaenoicacid(DHA,22:6n-3)andarachidonicacid(AA,20:4n-6)intotal lipid, 16:0, 18:0, 18:1n-9, eicosapentaenoic acid (EPA, 20:5n-3), DHA and AA in PL, 16:0, 16:1n-7, 18:1n-9, linoleic acid (LA, 18:2n-6), AA, EPA, DHA and docosapentaenoic acid (22:5n-3) in TAG extracted from the liver of S. triostegus in all seasons. N-3/n-6 ratio was found 2.00-2.61 in females, 1.15-2.75 in males in total lipid. The highest lipid content was found in May (2.39%) in the females.In the males, the highest level was found in September (2.91%). In TAG fraction, the component with the lowest ratio in both sexes’ TAG is PUFA. In PL fraction, SFA, MUFA, and PUFA percentages were found at similar rates in both sexes in all months.